1900’LÜ YILLARDA DOĞU’NUN ART NOUVEAU ÜSLUBU: İSTANBUL VE BAKÜ MİMARİ ÖRNEKLERİ. - BURNAK, Terane (Black Sea / Karadeniz, 2021)
In the 19 century, the Turkish and Azerbaijani architecture covered a way basically parallel to the development of architecture in the West. Since 1830s, the classicism in the Turkish and Azerbaijani architecture, and in the same way in the West European one, was forced out by retrospective imitations of historical architectural styles. With that in mind, architects pursued the objective to renovate and enrich full range of tools and methods based on outdated decorative fixtures. In the late 19- by the turn 20 centuries, aspirations to bring the architecture and construction together and thereby form an appropriate estimate gave an impetus to the advent of a new trend in architecture referred to as Art Nouveau. At the same time, the reviewed period was marked by formation of main principles and methods of the Turkish and Azerbaijani architecture that had sway over the new architecture of these countries. Testifying to the development of cultures of these countries later 19-earlier 20 centuries was enhanced diversity of edifices and buildings. Note that these structures preserved their genuineness along with local variations and in keeping with European cannons. Proceeding from the analysis of stylistic peculiarities of Turkish and Azerbaijani traditional forms and methods, technical and stylistic specificities of Art Nouveau, decorative-artistic solutions and symbols of forms in the architecture of Istanbul and Baku, it can therefore be concluded that the reviewed period mattered most in the architecture development. In view of this, the novelty of studies comes not from traditionalism but new approaches to the insight into forms, architectural planning and constructive peculiarities through identifying a place of the Turkish and Azerbaijani architecture in the history of the world architecture. The foregoing revealed the fact that the Turkish and Azerbaijani architecture made a weighty contribution to the development of the world architectural heritage of the end 19-beginning 20 centuries. The point at issue is about conditions predetermining the development of new spatial-dimensional, architectural-design and constructive peculiarities of the Turkish and Azerbaijani architecture, as well as the development of residential-public buildings and basic typological groups of these edifices.